The Artificial Lighting Analysis of Study Rooms in Dormitories and Classrooms Islamic Boarding School Of Lil Banat Parepare - Nimah Natsir; Nurul Jamala; Asniawaty Kusno (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2021)
This study aims to find out the intensity of light in the study room of Islamic boarding school of DDI Lil Banat Parepare. Measurements are taken in rooms that are often used by students to learn, namely classes and dormitories. The type of research used is quantitative by simulation method. Variables are tied to exposure measurement i.e. light intensity. While the variables are free, namely the arrangement of light points and the layout of the study room. Measurements were carried out over three days using a digital lux meter tool. The measurement results showed that the intensity of light in the dormitory did not meet the Indonesian National Standard for study space both night and day. During the day classrooms meet Indonesian National Standards but not at night. Although students as a space user is comfortable with the condition of light intensity in the study room and can learn according to these conditions, students still feel some complaints in the form of sore eyes, tense eyes and difficulty focusing. Thus, researchers made recommendations on the design of study rooms that can make students more comfortable learning in dormitories and classrooms so as to reduce complaints while studying. Lighting design recommendations are made in several alternatives by adding the number of lamps and changing the type of lamp using Dialux simulation. The simulation results of the study room lighting design recommendations have met the standards for use so that it can be applied to dormitories and classes at the Islamic boarding school of DDI Lil Banat Parepare. Keywords: Artificial lighting design; study room; light intensity